THE EFFECT OF SELF-ESTEEM ON GENDER AND BUDGETARY SLACK RELATIONSHIP: EXAMINING GENDER SOCIALIZATION THEORY - Solihah, Solihah; Rohma, Frida Fanani (Universitas Multimedia Nusantara, 2024)
Abstract” This research investigates further the moderating effect of self-esteem on gender relations on budgetary slack.This research examines the relationship between gender and budgetary slack. More than that, this study also analyzes the moderating effect of self-esteem on the relationship between gender and budgetary slack tendencies. During budgeting, subordinates try to avoid risks by doing budgetary slack. However, the perspective of gender socialization theory explains that there are differences in behavior in that women tend to avoid risks and are prone to depression compared to men. This study adds a new addition to budgetary slack literature based on informational characteristics attributes. Previous research on slack was limited and primarily focused on slack created by organizational factors. This study also enriches slack literature using an experimental design This study used an experimental method with a 2 x 2 factorial design between subjects and involved accounting students as participants. The findings show that slack tends to be more significant for male than female participants. The results of this study also show that self-esteem has a positive effect on budgetary slack tendencies. However, the research findings showed no interaction between the two variables. Differences in individual risk preferences concerning different genders are one of the primary keys to explaining the occurrence of dysfunctional behavior in activities that occur in organizations, especially when it comes to budgeting. This research implies that understanding individual personality based on gender is crucial in minimizing budgetary slack to determine the company. These findings can be considered regulators in designing effective control mechanisms by elaborating gender personality with individual self-esteem. Keywords: Budgetary Slack; Gender; Risk Preference; Self Esteem